Effect of cycle time and airflow in biological nitrogen removal from poultry slaughterhouse wastewater using sequencing batch reactor - Lopes,Carla L. (2015)
This study aimed to evaluate the influence of airflow (0.25, 0.50 and 0.75 L.L-1.min-1) and cycle time (10.45 h, 14.25 h and 17.35 h) on a sequencing batch reactor (SBR) performance in promoting nitrification and denitrification of poultry slaughterhouse wastewater. The operational stages included feeding, aerobic and anoxic reactions, sedimentation and discharge. SBR was operated in a laboratory scale with a working volume of 4 L, keeping 25% of biomass retained inside the reactor as inoculum for the next batch. In the anoxic stage, C: N ratio was maintained between 5 and 6 by adding cassava starch wastewater. A factorial design (22) with five repetitions was designed at the central point to evaluate the influence of cycle time and airflow on total inorganic nitrogen removal (N-NH4++N-NO2-+N-NO3-) and in the whole process (nitrification and denitrification). The highest total inorganic nitrogen removal (93.3%) was observed for airflow of 0.25 L.L-1.min‑1 and a cycle time of 14.25 h. At the end of the experiment, the sludge inside the reactor was characterized by fluorescent in situ hybridization (FISH), indicating the presence of ammonia and nitrite oxidizing bacteria.